2009
DOI: 10.1177/0091270009337509
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Impact of Xuezhikang on Cardiovascular Events and Mortality in Elderly Hypertensive Patients With Previous Myocardial Infarction From the China Coronary Secondary Prevention Study (CCSPS)

Abstract: Coronary heart disease, hypertension, and dyslipidemia are highly prevalent and commonly coexist in people who are middle-aged and older. Previous data suggested that lowering cholesterol concentrations in individuals at high risk of cardiovascular disease improved clinical outcomes. Xuezhikang, a partial extract of red yeast rice containing statin, has a marked impact on lipids. The purpose of this study, therefore, was to evaluate the impact of Xuezhikang on reducing cardiovascular events and mortality in el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…1,2 The results of this study thus add to the existing evidence for the use of red rice yeast extract in hyperlipidaemia. 1,2 The results of this study thus add to the existing evidence for the use of red rice yeast extract in hyperlipidaemia.…”
Section: Commentarysupporting
confidence: 57%
“…1,2 The results of this study thus add to the existing evidence for the use of red rice yeast extract in hyperlipidaemia. 1,2 The results of this study thus add to the existing evidence for the use of red rice yeast extract in hyperlipidaemia.…”
Section: Commentarysupporting
confidence: 57%
“…More recently, a double-blind, multicenter trial in China has demonstrated, in 4870 patients with a previous MI and high total cholesterol levels after 4.5 years followup, that xuezhikang administration (a commercial red yeast rice preparation) at a dose of 0.6 g twice daily was associated with a reduction in the incidence of major coronary events, including nonfatal MI and death from CHD compared to placebo (5.7% vs. 10.4%) [51]. Subsequent subgroup analyses of this trial have further supported these observations by confirming a reduction in cardiovascular outcomes among diabetics and in the elderly [52]. In addition, Xuezhikang has also shown, in small clinical trials, to effectively improve endothelial function in patients with coronary artery disease (CAD) [53].…”
Section: Cholesterol-lowering Natural Agents: Sterols/stanols and Redmentioning
confidence: 56%
“…15, 16, 17 However, some trials have found null results. 18, 19, 20, 21 Numerous randomized controlled trials have been conducted in China to evaluate the efficacy of novel Chinese herbal formulas generated from well-known Chinese medicine formulas or from currently effective practices to treat hypertension. Some trials have effectively treated hypertension.…”
Section: Introductionmentioning
confidence: 99%